PENINGKATAN KETERAMPILAN MENULIS BAHASA ARAB MELALUI STRATEGI BROKEN SQUARE/TEXT PADA SISWA KELAS VII SMP MUHAMMADIYAH 2 PONTIANAK - Mislaini, Mislaini; Arifudin, Arifudin (Institut Agama Islam Negeri Pontianak, 2024)
This study aims: 1) To find out the Arabic writing skills of seventh grade students of SMP Muhammadiyah 2 Pontianak before using Broken Square/Text strategy in Arabic language learning. 2) To find out the implementation process of Broken Square/Text strategy in Arabic language learning. 3) To find out the improvement of Arabic writing skills of seventh grade students after using Broken Square/Text strategy. This research is a Class Action Research (CAR) with two cycles. The subjects in this study were students of class VII SMP Muhammadiyah 2 Pontianak which amounted to 32 students. Data collection techniques in this study were carried out through tests, observation and documentation. And data analysis using percentages and indicators of success. Based on the results of the study, it is known that there are 32 students in total, which in the pre-cycle activities the percentage of student completeness only reached 34.37% with an average score of 63.28. In cycle I after using the Broken Square/Text strategy the percentage of student completeness increased to 62.5% with an average of 72.03. Due to not meeting the standards, cycle II was carried out with the results of the percentage of completeness reaching 78.12% and an average of 79.06. Therefore, the researcher concluded that using the Broken Square/Text strategy in learning Arabic can significantly improve students' writing skills, and foster students' enthusiasm in learning Arabic.